2006
DOI: 10.1677/jme.1.01937
|View full text |Cite
|
Sign up to set email alerts
|

Leptin resistance following over-expression of protein tyrosine phosphatase 1B in liver

Abstract: Obesity is typically associated with resistance to leptin, yet the mechanism by which leptin signaling becomes impaired is poorly understood. Here we sought to determine if the development of obesity and leptin resistance correlates with increased expression of protein tyrosine phosphatase 1B (PTP1B) in peripheral tissues and whether over-expression of this phosphatase, specifically in liver, could alter the leptin-mediated effects on feeding and glucose metabolism. Obesity was induced in mice through a high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Conversely, no proliferative action of leptin has been found in experiments with islets from adult rats (Okuya et al 2001). Recent studies with disruption of the leptin receptor either in the pancreas (Morioka et al 2007) or in b-cells and hypothalamus (Covey et al 2006) indicate that leptin may have a negative role in b-cell mass expansion, since the average size of the islets from these KO mice was found to be increased. In one of these studies, no modification of proliferation was observed (Morioka et al 2007).…”
Section: Regulation Of B-cell Mass By Leptinmentioning
confidence: 97%
See 4 more Smart Citations
“…Conversely, no proliferative action of leptin has been found in experiments with islets from adult rats (Okuya et al 2001). Recent studies with disruption of the leptin receptor either in the pancreas (Morioka et al 2007) or in b-cells and hypothalamus (Covey et al 2006) indicate that leptin may have a negative role in b-cell mass expansion, since the average size of the islets from these KO mice was found to be increased. In one of these studies, no modification of proliferation was observed (Morioka et al 2007).…”
Section: Regulation Of B-cell Mass By Leptinmentioning
confidence: 97%
“…Both proteins work as negative regulators of leptin-induced activation of the JAK/STAT pathway (Morris & Rui 2009). In addition to central leptin resistance, several studies on obesity models have observed attenuated leptin signaling in peripheral tissues (Prpic et al 2003, Lam et al 2006, Steinberg et al 2006, Nave et al 2008. In most cases, an increase in PTP1B or SOCS3 levels was associated with this attenuated response to leptin.…”
Section: Leptin Resistancementioning
confidence: 99%
See 3 more Smart Citations